Altered Serum Tumor Necrosis Factor and Interleukin-1β in First-Episode Drug-Naive and Chronic Schizophrenia - Zhu, Furong; Zhang, Lulu; Liu, Fang; Wu, Renrong; Guo, Wenbin; Ou, Jianjun; Zhang, Xiangyang; Zhao, Jingping (Frontiers in Neuroscience, 2018)
Objective: Abnormality of the immune system might play a significant role in the pathogenesis of schizophrenia. We want to identity whether the serum TNF-α and IL-1β levels were changed in FEDN patients and CP and to investigate the relationship between both cytokines and psychopathological symptoms. Methods: We recruited 69 FEDN patients, 87 CP and 61 healthy controls. Schizophrenia symptomatology was evaluated with the Positive and Negative Syndrome Scale (PANSS), the Scale for the Assessment of Negative Symptoms (SANS) and Clinical Global Impression Scale (CGI). Serum TNF-α and IL-1β levels were examined using sandwich enzyme-linked immunosorbent assay (ELISA). Results: TNF-α and IL-1β levels in CP were significantly higher compared to healthy controls, but TNF-α and IL-1β levels in FEDN patients were significantly lower than in both CP and healthy controls. A moderate correlation between serum TNF-α or IL-1β levels and PANSS negative subscore was found in CP. But there was no correlation between altered cytokines and clinical symptoms in FEDN patients. Conclusions: Increased TNF-α and IL-1β levels in chronic patients may be associated with the progression, psychotropic drugs or other factors occur during chronic stage. Immune modulating treatments may become a new strategy of therapy for this subgroup of patients.